Measuring, evaluating and improving the effectiveness of invasive predator control programs: Feral cat baiting as a case study. (15th February 2021) - Fancourt, Bronwyn A.; Augusteyn, John; Cremasco, Peter; Nolan, Barry; Richards, Samuel; Speed, James; Wilson, Cameron; Gentle, Matthew N.
Abstract: Reducing the impacts of invasive predators is a key objective for conservation managers, livestock producers and human health agencies globally. The efficacy of invasive predator control programs, however, is highly variable. To improve control efficacy, managers require a fundamental understanding of the factors that contribute to the success or failure of a control program. Using a predator baiting program as a case study, we measured the efficacy of baiting as a control tool to significantly reduce feral cat ( Felis catus ) populations. We used camera traps and cat-borne GPS collars to monitor changes in feral cat populations at a baited site and an unbaited site, using a Before-After, Control-Impact (BACI) design. We also identified five key elements required for a successful baiting program (bait encounter rate, availability, attractiveness, palatability and lethality) and simultaneously measured these to identify areas for potential improvement. Baiting was ineffective at reducing feral cat populations; collared cat mortality was only 11% (1/9), with camera traps revealing negligible reductions in the number of cat detection events (9%), naïve occupancy (15%), and no significant change in the relative abundance of feral cats ( F 1, 54  = 0.8641, P  = 0.357). Several factors contributed to the poor control efficacy. Bait encounter rates were low, with cats active along tracks (where baits were laid) < 4% of the time. Cats encountered only 14% (7/50) of monitored baits, but none were eaten. Initially, baits appeared attractive to cats; however meat ants and desiccation rapidly decreased bait palatability. Bait availability to cats declined rapidly, with 36% of monitored baits (18/50) removed by non-target species within the first 48 h. The mortality of one collared cat and chemical assays confirmed that, on average, each bait contained sufficient 1080 to kill a large (>5 kg) feral cat. Our findings suggest that altering bait deployment patterns, increasing bait densities and improving bait palatability could potentially improve the efficacy of baiting programs to reduce feral cat populations. Our study provides a framework to measure and evaluate the key elements that contribute to efficacy of pest control programs, and to identify opportunities for improving outcomes of future control programs. Highlights: Invasive predator control programs often achieve variable levels of success. To be effective, control tools such as baits need to be encountered, available, attractive, palatable and lethal. To increase control efficacy, we need to understand these criteria and how they could be improved. Low bait encounter rates, availability and rapid unpalatability contribute to failure of feral cat baiting programs. Increased baiting densities, off-track deployment and improved palatability could increase efficacy of feral cat baits.